SERVICE QUALITY AND TRUST ON INCREASING CONSUMER SATISFACTION - Kurniawan, Pebi; Jufri, Ali (Dinasti International Journal of Digital Business Management, 2022)
The purpose of this study was to determine and analyze: (1) service quality; (2) Trust; (3) Consumer Satisfaction and (4) The Influence of Service Quality Performance and Trust on Patient Satisfaction at the Cirebon Regional General Hospital. The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this study is the patients of the Cirebon Regional General Hospital with a sample of 50 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the performance of service quality according to patients at the Cirebon Regional General Hospital was generally not good; Trust according to patients at the Cirebon Regional General Hospital is generally good and patient satisfaction at the Cirebon Regional General Hospital is currently considered good. Service quality and trust have an effect on patient satisfaction at the Cirebon Regional General Hospital. Because trust affects consumer satisfaction dominantly, the Cirebon Regional General Hospital must maintain conditions so that patient satisfaction at the Cirebon Regional General Hospital remains consistent, so that customer satisfaction is formed strongly and deeply rooted.